Jenis Dan Peran Pentingnya Alat Pemadam Api Ringan Di Pesawat Boeing 737- 400 Dalam Keadaan Darurat - Damara Zerlina Putri Elysia; Michael Sagoro; Rizka Dewi Nur Auliana; Hadi Prayitno; Soon Yong Ang (Indonesia Civil Pilot Academy Banyuwagi, 2025)
Light fire extinguishers are important for maintaining the safety of passengers and crew during flights, especially on commercial aircraft such as the Boeing 737-400. This research aims to analyze the types and important roles of Portable Fire Extinguishers (PFE) available on the Boeing 737-400 aircraft in fire emergency situations. This research uses a descriptive qualitative method with a case study approach on the Boeing 737-400 aircraft. Data were obtained through literature study and field observation. The research results show that on the Boeing 737-400 aircraft, lightweight fire extinguishers are used with dry chemicals or gases suitable for the conditions on the aircraft. Both types of equipment are effective in extinguishing fires without endangering passengers, cabin crew, and surrounding electronic equipment. Various types of extinguishing agents and spray systems can enhance the efficiency of lightweight fire extinguishers in the air. This research is expected to make flights safer by protecting passengers, crew members, and aircraft from fire risks, and also for airlines to enhance routine training for cabin crew on the use of portable fire extinguishers in various fire scenarios.